2004
DOI: 10.1136/fn.89.1.f57
|View full text |Cite
|
Sign up to set email alerts
|

Acellular pertussis vaccine given by accelerated schedule: response of preterm infants

Abstract: Objective: To describe the immune response of preterm infants to a diphtheria/tetanus/three component acellular pertussis (DTaP) vaccine, under an accelerated schedule, and the effects of steroids on this response. To compare responses with those of term infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 12 publications
4
30
0
Order By: Relevance
“…12 Similar results were reported by Berrington et al who showed that all premature infants developed an average response of >0.52 IU/ml using a 2, 3 and 4 month schedule and that there was no statistically significant difference to term infants. 13 Kitchin et al compared two groups of healthy term infants given either DTaPIPV-Hib (Pediacel) and Men C, or DTwP-Hib, Men C and OPV at 2, 3 and 4 months of age.…”
Section: Immunogenicitysupporting
confidence: 79%
See 2 more Smart Citations
“…12 Similar results were reported by Berrington et al who showed that all premature infants developed an average response of >0.52 IU/ml using a 2, 3 and 4 month schedule and that there was no statistically significant difference to term infants. 13 Kitchin et al compared two groups of healthy term infants given either DTaPIPV-Hib (Pediacel) and Men C, or DTwP-Hib, Men C and OPV at 2, 3 and 4 months of age.…”
Section: Immunogenicitysupporting
confidence: 79%
“…On the basis of these findings it is concluded that consideration should be given to an additional dose of PnC for infants born at ≤32 weeks: however, because of the schedule change from 3 doses to 2 doses (at 2 and 4 months) and the replacement of the 7 valent preparation by Prevenar 13, which has an additional 6 serotypes with all 13 components having 10% more capsular saccharide than Prevenar, it will be necessary to evaluate the immunogenicity of this new vaccine in premature infants. 12 Kitchin et al found that PT, FIM and PRN antibody responses were higher in healthy term infants given DTwPHib-OPV than those given Pediacel (with an acellular pertussis preparation)-FHA levels were higher in the Pediacel group. In summary, data suggest that premature and term infants given a 3 course acellular pertussis program using a 2, 3 and 4…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 presents data from a vaccine study demonstrating the competing influences of gestational age, maternal antibody, and age at third vaccination on the vaccine response of preterm infants. 37 In particular, it demonstrates the independent and critical effect of gestational age on antibody responses to vaccine antigens.…”
Section: T Cell Responsesmentioning
confidence: 97%
“…The work of S. Esposito et al, who revealed sufficient levels of specific immune globulins at the age of 5 years in most premature infants who undergone a three-stage vaccination (scheme -3-5-12 months), indicates the long-term preservation of protective levels [29]. A range of studies claim that premature infants with GA <31 weeks respond to the acellular vaccine administration not only humorally, but also cellularly -with the IFN γ production by peripheral mononuclear leukocytes and the interleukin (IL) 5 and IL 13 secretion in case of exposure to vaccinal antigens [30]. Inactivated poliomyelitis vaccine.…”
Section: Immunogenicity and Reactogenicity In Premature Infantsmentioning
confidence: 99%